Transanal endoscopic microsurgery for large benign rectal tumors; where are the limits?. (May 2016) - Khoury, Reem; Duek, Simon D.; Issa, Nidal; Khoury, Wisam
Abstract: Introduction: Local excision is the treatment of choice for large benign rectal lesions. Transanal endoscopic microsurgery is recommended. The excision of large lesions >4 cm has been previously described. We report our series of lesions >5 cm that have been excised via the transanal endoscopic microsurgery. Methods: Patients who underwent transanal endoscopic microsurgery for rectal tumors, between the years 2002–2012, were identified. Patients with tumors greater than 5 cm consisted the study group. Tumor diameter was determined based on fresh specimen measurements. Data pertaining to patients and tumor characteristics, operative and histopathology findings, postoperative outcomes were collected. Local recurrence and effects on anal sphincter function were assessed. Results: Twenty five patients (14 female) with mean age of 70.3 ± 10.1 years, met the inclusion criteria. The mean tumor size was 5.7 ± 0.9 cm. The median distance from anal verge was 8 cm (range 1–17). Preoperative biopsy of the rectal tumor revealed adenoma with/without dysplasia in 24 patients. Postoperative findings were adenoma with/without dysplasia in 20 patients, T1 rectal cancer in 4 patients and tail gut cyst in one patient. Free margins were documented in 17 patients, in 7 it was involved and in one patient it could not be determined. In 2 cases the procedure was discontinued. Except for nonspecific transient fever no postoperative complications were reported. After a median follow up of 24.2 months, the 3-year LR rate was 10.9%. Conclusion: TEM is feasible for the treatment of large benign rectal tumors. It may be an alternative method for proctectomy in selected patients with large rectal lesions.